The 117-story treehouse - Griffiths, Andy, 1961- (New York : Feiwel and Friends, 2019)
For all the books they have written, Andy is the narrator and Terry is the illustrator, but when Terry tries to narrate too, the story goes out of control and they must evade the Story Police, who want to arrest them for crimes against storytelling.
2.9.
3-6.
580L
Keywords: Tree houses -- Juvenile fiction; Imagination -- Juvenile fiction; Books and reading -- Juvenile fiction; Authors -- Juvenile fiction; Illustrators -- Juvenile fiction; Humorous stories; Tree houses -- Fiction; Imagination -- Fiction; Books and reading -- Fiction; Authors -- Fiction; Illustrators -- Fiction; Humorous stories; Humorous fiction